The Effect of Use of Animation Video Media on Retelling Story Skills - Novita Puspa Dewi; Sudarmin Sudarmin; Sri Wardani; Deni Setiawan; Edi Waluyo; Selviana Selviana (International Journal of Active Learning, 2023)
This research is a quasi-experimental study that aims to determine whether there is an effect of using video animation media in learning the retelling skills of class IV SDN 141 Pinrang. The independent variable in this research is video animation media and the dependent variable is the skill of retelling fictional stories. The approach of this research is quantitative with a Quasi Experimental type, with a research plan of Noneequivalent Control Group Design. The population in this study were all 4th grade students of SDN 141 Pinrang Kecamatan Marioriawa PinrangÂ  Regency as many as 2 classes, while the sample was class IVa as a control class with 15 students and class IVb as an experimental class with 15 students. Data collection methods are speaking tests, observation sheets and documentation. The research data were obtained by giving a skill test of retelling a fictional story in the form of a pretest and posttest. The data analysis technique used is descriptive statistical analysis and inferential statistical analysis consisting of hypothesis testing using independent sample T-test. Based on the results of inferential statistical analysis, the value of P = 0.000 is smaller than the value of = 0.05. It can be concluded that there is an effect of using animated video media fiction text on the retelling skills of fourth grade students at SDN 141 Pinrang Kecamatan Marioriawa, Pinrang Regency.